Pengaruh Model Pembelajaran Team Assisted Individualization (TAI) dan Pengelolaan Kelas Terhadap Motivasi Belajar PPKn Peserta Didik - Mufti Syaifuddin; Imam Suyitno; Mustari Mustari (Phinisi Integration Review, 2020)
This study aims to determine; (i) whether there is a positive and significant influence on the Team Assisted Individualization (TAI) model and classroom management on the learning motivation of students PPKn at SMP Negeri 8 Makassar, (ii) whether there is a positive and significant effect of the Team Assisted Individualization (TAI) model on the learning motivation of students PPKn at SMP Negeri 8 Makassar, (iii) whether there is a positive and significant influence of classroom management on the learning motivation of PPKn learners at SMP Negeri 8 Makassar. This type of research used in this research is quantitative with survey methods. The population in this study were all students of class VIII SMP Negeri 8 Makassar, amounting to 440. The sampling technique was Simple Random Sampling technique with a total sample of 195. Data collection techniques used were collected through questionnaire, and documentation.The results of this study indicate that (i) there is a positive and significant influence on the Team Assisted Individualization (TAI) model and classroom management on the learning motivation of students PPKn at SMP Negeri 8 Makassar. Shown with the Fcount value of 108.104 > Ftable 3.04. While the significance level is 0,000 < 0.05 and simultaneously there are 53% of the contribution of the Team Assisted Individualization (TAI) model and classroom management to the learning motivation of students PPKn at SMP Negeri 8 Makassar. (ii) there is a positive and significant influence between the Team Assisted Individualization (TAI) learning model on the learning motivation of students PPKn at SMP Negeri 8 Makassar. Shown by the tcount 12, 749 > ttable 1.645 with a significance of 0.000 < 0.05. and (iii) there is a positive and significant effect between classroom management on students' learning motivation of PPKn at SMP Negeri 8 Makassar. Shown tcount 11, 365 > ttable 1.645 with a significance of 0,000 < 0.05